Combined process of bio-contact oxidation-constructed wetland for blackwater treatment - Jin, Zhan; Zheng, Yangfei; Li, Xiangyu; Dai, Chuanjun; Xu, Kaiqin; Bei, Ke; Zheng, Xiangyong; Zhao, Min (Bioresource Technology, 2020)
•A combined system bio-contact oxidation and CW is presented for blackwater treatment.•Effects of HRT and particle size on treatment performance were studied.•Microbial communities in the combined system were characterized.•Removal efficiency of COD, TN, NH4+-N, and TP are reported under varying conditions.•1–3 mm particle size and 3-d HRT were the optimal conditions for nutrient removal. In this study, a combined process of bio-contact oxidation and constructed wetland for blackwater treatment was assessed. The effects of hydraulic retention time and particle size on treatment performance were systematically studied. Additionally, microbial communities in the combined process were characterized. The results show that the removal efficiency of COD, TN, NH4+-N, and TP under optimum conditions in this study were 81.6%, 56.1%, 42.2%, and 73.7%, respectively. The maximum nitrogen removal rate reached 16.5 g m−2 d−1 (3 d). N and P removed via direct plant absorption accounted for only 19.7% and 16.1% of the total system, respectively. Plants play a crucial role in the microbial community of constructed wetlands and influence the overall performance of the system. The biofilm on roots favored aerobic and heterotrophic bacteria such as the aerobic denitrification microorganisms of Pelagibacterium, Halomonas, and Zoogloea. Overall, the combined process is a suitable technique for the treatment of blackwater.